Racial and Ethnic Differences in Parental Decision-Making Roles in Pediatric Oncology - Sisk, Bryan A. (J Palliat Med, 2020)
Background: Prior work in adult oncology suggests minority patients are less involved in decision making than preferred. However, few studies have explored decision-making experiences of minority parents in pediatric oncology. Objective: To determine whether parental decision-making preferences and experiences vary by race/ethnicity. Design: Questionnaire-based cohort study. Setting/Subjects: Three hundred sixty five parents of children with cancer and their oncologists at two academic centers. Measurements: Parents reported on preferred and actual decision-making roles. Associations between race/ethnicity and decision-making outcomes determined by chi-squared test. Results: Most parents preferred shared decision making (235/368, 64%), whereas 23% (84/368) preferred parent-led decision making and 13% (49/368) preferred oncologist-led decision making. Parental decision-making preferences did not differ by race/ethnicity (p = 0.38, chi-squared test). However, the actual role parents played in decision making differed by parental race/ethnicity, with 25% (71/290) of white parents reporting parent-led decision making, versus 37% (9/24) of black parents, 48% (13/27) of Hispanic parents, and 56% (15/27) of Asian/other parents (p = 0.005, chi-squared test). Oncologists accurately predicted parental preferences for decision making 49% of the time (n = 165/338), but accuracy also differed by race and ethnicity. Oncologists accurately predicted parental preferences for 53% of white parents (140/266), 23% of black parents (5/22), 37% of Hispanic parents (10/27), and 43% of Asian/other race parents (10/23) (p = 0.026, chi-squared test). Conclusions: Minority parents held more active roles than white parents, and oncologists had more difficulty predicting decisional preferences for minority parents relative to white parents. These findings suggest that minority parents are at risk of inferior decision-making experiences.